Implementation of Leverage, Profitability, Company Size, Fixed Asset Intensity, and Capital Intensity on Tax Avoidance (Empirical Study on Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesia Stock Exchange in 2020 – 2022) - Ines Dyah Ayu Hapsari; Setiawati, Erma (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines the determinants of tax avoidance in the consumer goods sector listed on the Indonesia Stock Exchange from 2020 to 2023 using multiple linear regression. While the method is appropriate, the low R-squared value (24.7%) indicates that key factors such as corporate governance, ownership structure, or international operations may have been omitted, limiting the model’s explanatory power. The Cash Effective Tax Rate (CERT) is used as a proxy for tax avoidance due to its common use in literature; however, it may be influenced by temporary differences or one-off tax items, potentially masking consistent tax planning behavior. Acknowledging this limitation, future research should consider multi-metric approaches and broader variables to capture a more comprehensive picture. Due to sector-specific characteristics, the findings may not be generalizable across industries.